Eine Siedlungskammer der späten Römischen Kaiser- und Völkerwanderungszeit von Flintbek, Kreis Rendsburg-Eckernförde - Müller, Eric (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The area around Flintbek in the Rendsburg- Eckernförde district was previously known primarily for the numerous grave fi nds from the Stone and Bronze Ages. Settlements were hardly detectable. Archaeological sites from the late Roman and Migration Periods have so far been completely absent. During 2020 and 2021, three excavations took place as part of the development of new building areas in the periphery of Flintbek. The sites are settlements from the late Roman Iron Age and Migration Period with numerous structures and homesteads. These sites are special, not just because they are the first evidence of sites of this date in the Flintbek area, but above all because of the very well-preserved settlement structures. Noteworthy are the types of houses that are rare and unusual for the area. Socalled corridor houses appear at the Flintbek sites LA 186 and LA 192, which were previously only known from two other sites in Schleswig-Holstein. Outstanding, however, are the strong influences in house construction from the north or the area of northern Schleswig-Holstein and southern Jutland that can be observed on all three settlement areas, which were previously rarely seen in this form for the Holstein area. The Jutlandic influence manifests itself more clearly in the form of ship-shaped house plans and houses that have their best parallels on Danish sites such as Vorbasse. There are also mixed forms that point to both northern and eastern traditions. Paved paths and squares also point to connections to the north, which until now were virtually unknown to settlements of this time on the Schleswig-Holstein mainland.